2013
DOI: 10.1073/pnas.1306534110
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1promotes the ubiquitination of PCNA and recruitment of translesion polymerases in response to replication blockade

Abstract: Breast cancer gene 1 ( BRCA1 ) deficient cells not only are hypersensitive to double-strand breaks but also are hypersensitive to UV irradiation and other agents that cause replication blockade; however, the molecular mechanisms behind these latter sensitivities are largely unknown. Here, we report that BRCA1 promotes cell survival by directly regulating the DNA damage tolerance pathway in response to agents that create cross-links in DNA. We show that BRCA1 not only promotes efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 39 publications
3
44
0
3
Order By: Relevance
“…A key event in regulation of TLS is the monoubiquitination of PCNA (34,37,53,54). PCNA is monoubiquitinated in response to DNA damage induced by UV or other chemical reagents, such as mitomycin C (MMC), hydroxyurea (HU), methyl methanesulfonate (MMS), and aphidicolin (55)(56)(57). We found that monoubiquitination of PCNA in response to UV treatment is enhanced in the presence of LANA.…”
Section: Discussionmentioning
confidence: 94%
“…A key event in regulation of TLS is the monoubiquitination of PCNA (34,37,53,54). PCNA is monoubiquitinated in response to DNA damage induced by UV or other chemical reagents, such as mitomycin C (MMC), hydroxyurea (HU), methyl methanesulfonate (MMS), and aphidicolin (55)(56)(57). We found that monoubiquitination of PCNA in response to UV treatment is enhanced in the presence of LANA.…”
Section: Discussionmentioning
confidence: 94%
“…We speculate that the damage induced phosphorylation of BRCA1 may be involved. 43 Both BRCA1 and FancJ have well-established roles in DNA damage checkpoint and DNA repair which take place early during DDR. DDICA occurs much later (often a few days later).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] We recently showed that prolonged treatment of 2 ICLs, MMC and cis-platin, also induces pronounced centrosome amplification, 38 suggesting that the induction of centrosome amplification is likely an integral part of DDR. Because BRCA1 is such an important DDR protein and is modified and stabilized during sustained DNA damage, 26,27,43 we then investigated whether BRCA1 is also involved in DDICA. Interestingly, depletion of BRCA1 reduced the MMC-and HU-induced centrosome amplification by about 30-50% ( Fig.…”
Section: Brca1 Promotes Dna Damage-induced Centrosome Amplificationmentioning
confidence: 99%
“…In addition to the major E3 ubiquitin ligase RAD18, several other E3 ligases, like RNF8 (Zhang et al, 2008) and CRL cdt2 (Terai et al, 2010), have been reported to regulate PCNA-mUb. Additionally, many factors, including apoptosis regulatory protein Siva (SIVA1) (Han et al, 2014), Spartan/C1orf124 [ protein with sprT-like domain at the N-terminus, also known as DNA damage protein targeting VCP (DVC1)] (Centore et al, 2012), MutS protein homolog 2 (MSH2) (Zlatanou et al, 2011;Lv et al, 2013), breast cancer 1 (BRCA1) (Tian et al, 2013), have also been found to regulate the RAD18-dependent PCNA-mUb. Ubiquitin-specific protease 1 (USP1) also participates in the regulation of PCNA-mUb as a key deubiquitylase (DUB) for deubiquitylating PCNA-mUb (Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%